El Workshop on Engineering Applications 2016: Avanzando hacia el Reconocimiento Internacional - Figueroa García, Juan Carlos; López Santana, Eduyn Ramiro; Ferro Escobar, Roberto (Ingeniería, 2017)
Workshop on Engineering Applications 2016: A Step Closer Towards International Recognition Language: English